208k views
3 votes
3 ( x + 2 ) = 4 ( x + 1 )

User Hagakurje
by
5.4k points

2 Answers

4 votes

Answer:

x=2

Explanation:

User Volex
by
5.0k points
4 votes

Answer:

x = 2

Explanation:


3(x+2)=4(x+1)\qquad\text{use the distributive property:}\ a(b+c)=ab+ac\\\\(3)(x)+(3)(2)=(4)(x)+(4)(1)\\\\3x+6=4x+4\qquad\text{subtract 6 from both sides}\\\\3x+6-6=4x+4-6\\\\3x=4x-2\qquad\text{subtract}\ 4x\ \text{from both sides}\\\\3x-4x=4x-4x-2\\\\-x=-2\qquad\text{change the signs}\\\\x=2

User Mehdi Saman Booy
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.